2019
DOI: 10.1016/j.meegid.2019.04.023
|View full text |Cite
|
Sign up to set email alerts
|

Detection and spike gene characterization in porcine deltacoronavirus in China during 2016–2018

Abstract: A B S T R A C TPorcine deltacoronavirus (PDCoV) has been emerging in several swine-producing countries for years. In our study, 719 porcine diarrhoea samples from 18 provinces in China were collected for PDCoV and porcine epidemic diarrhoea virus (PEDV) detection. The epidemiological survey revealed that the positive rates of PDCoV, PEDV and coinfection were 13.07%, 36.72% and 4.73%, respectively. The entire spike (S) genes of eleven detected PDCoV strains were sequenced. Phylogenetic analysis showed that the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
36
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(38 citation statements)
references
References 33 publications
(38 reference statements)
1
36
0
Order By: Relevance
“…Compared with the USA/Japan/South Korea lineage and Vietnam/ Laos/Thailand lineage strains, the China lineage strains have 3-nt TAA deletions (52 N), leading to the lack of an asparagine in the S gene. This may be the most important feature of the Chinese lineage strains, except for CH/Jiangsu/2014 (Zhang et al, 2019d). Sequence analysis showed that 27 aa mutations were detected in S1 (Fig.…”
Section: Amino Acid Variants In the Spike Proteinsmentioning
confidence: 95%
See 2 more Smart Citations
“…Compared with the USA/Japan/South Korea lineage and Vietnam/ Laos/Thailand lineage strains, the China lineage strains have 3-nt TAA deletions (52 N), leading to the lack of an asparagine in the S gene. This may be the most important feature of the Chinese lineage strains, except for CH/Jiangsu/2014 (Zhang et al, 2019d). Sequence analysis showed that 27 aa mutations were detected in S1 (Fig.…”
Section: Amino Acid Variants In the Spike Proteinsmentioning
confidence: 95%
“…After nucleotide homology comparison and screening, 29 representative strains were selected from 102 strains for molecular evolutionary analyses (Tables 2 and S1). In addition, these strain sequences have been previously published as reference sequences (Suzuki et al, 2018;Zhang et al, 2019a, c;Zhang et al, 2019d). To obtain the sequence, the complete S protein, N protein and partial ORF1a genes were amplified in 10 PDCoV-positive samples ( Table 1).…”
Section: Primer Namementioning
confidence: 99%
See 1 more Smart Citation
“…Most of the reported Chinese strains were isolated from the eastern and central regions of China (Dong et al, 2016;Dong et al, 2015;Wang et al, 2015;Zhang et al, 2019c). Besides, PDCoV isolate, CHN-SC2015, was isolated from Sichuan Province in southwest China .…”
Section: Discussionmentioning
confidence: 99%
“… 3 Since then, the virus has been detected in many other countries, including Canada, mainland China, South Korea, Thailand, Laos, Vietnam, Japan, Mexico, and so on. 4 , 5 Clinically, PDCoV-infected pigs often present with diarrhea and/or vomiting, dehydration, and death of neonatal piglets. 6 The outbreak of PDCoV infection in numerous countries has resulted in considerable economic losses to the global swine industry.…”
Section: Introductionmentioning
confidence: 99%